DNA-Peptide Amphiphile Nanofibers Enhance Aptamer Function - Serrano, Christopher M. (ACS Appl Bio Mater, 2019)
The single stranded DNA oligonucleotides known as aptamers have the capacity to bind proteins and other molecules and offer great therapeutic potential. Further work is required to optimize their function and to diminish their susceptibility to nuclease degradation. We report here on the synthesis and supramolecular self-assembly of DNA-peptide amphiphiles that form high aspect ratio nanofibers and display aptamers for platelet-derived growth factor. The nanofibers were found to bind the growth factor with an affinity that was fivefold greater than the free aptamer. We also observed that the aptamer displayed by the supramolecular nanostructures was eight times more nuclease resistant than free aptamer. In order to highlight the therapeutic potential of these supramolecular systems, we demonstrated the improved inhibition of proliferation when the growth factor was bound to aptamers displayed by the nanofibers.